Attitudes and experiences regarding preventive strategies for the deaf population in Western New York. - Lorne Farovitch; Carol Padden; Edwin vanWijngaarden; Benjamin Miller; Brian Leydet; Timothy Dye (Public Library of Science (PLoS), 2023)
People for whom English is a second language, such as the deaf population, often have unequal access to health information and low health literacy. In the context of a wider study on risk of tick-borne illness in deaf communities, we explored barriers, opportunities, and nuances to accessible health information and communication among deaf people. Semi-structured qualitative individual and group interviews were conducted with 40 deaf people in upstate New York, to explore factors associated with health literacy and health information accessibility. Interviews were conducted in American Sign Language (ASL) by a deaf researcher fluent in ASL. Data analysis included the translation of ASL signs into English words, systematic coding, and generation of themes. A total of 21 interview events (mean time per interview = 41 minutes) were conducted. Two main themes and multiple sub-themes emerged from the data: 1) Layers of obstacles faced by deaf people confirms (or reinforces) exclusion; and 2) preventive information is unavailable or inaccessible to deaf people. Sub- themes identified in the results were perceptions of the deaf community and deaf culture, complex layers of obstacles faced by deaf individuals, the digital divide, the culture of communication, awareness of tick and tick-borne disease (TBD) diseases, importance of using certified deaf interpreters (CDI), health information dissemination strategies and collaborations with the education system, and physical/virtual community engagement. The data suggested several challenges to health literacy in the deaf population, including healthcare and education inequalities and negative perceptions of deaf people by both deaf and hearing people. Improving health literacy in the deaf population requires more interpreters who themselves are deaf ("certified deaf interpreters"), provision of health information in ASL, and a greater engagement with the deaf population by education and healthcare systems.